Learning from the Kenyan experiment: key takeaways for implementing managed equipment services in developing countries - Njagi, Ephantus; Iloka, Keneth; Wawira, Sasha; Thiga, Laban; Muraguri, Nicholas (Frontiers in Health Services, 2025)
BackgroundIn 2015, the Kenyan government signed 7-year contracts with 5 Original Equipment Manufacturers (OEMs) to improve healthcare accessibility and equity. The OEMs were to supply, install, maintain, and replace equipment and provide user training for 98 hospitals across Kenya's 47 counties through a Managed Equipment Services (MES) arrangement. This paper highlights the planning, procurement, and implementation of Kenya's first comprehensive MES arrangement.MethodsRetrospective review of the implementation process drawing data from program databases, reports, and other relevant sources.ResultsThe MES program was successfully implemented in Kenya for the first time to upscale specialised health infrastructure and expand critical healthcare services across the 47 counties. Previously unavailable services in the county's hospitals, such as dialysis, were set up in 49 hospitals, critical care units in 11 hospitals, and theatre, sterilisation, and imaging services were expanded in 98 hospitals. The program provided reliable equipment installation and maintenance, increased healthcare workers' capacity through training, and created a more conducive working environment. Key lessons learned include importance of defining detailed equipment specifications, ensuring comprehensive stakeholder engagement, and allowing sufficient time for assessment and implementation. Challenges encountered were prolonged procurement process, insufficient stakeholder buy-in, and delays in implementation.ConclusionsWe have described our experience of planning, procurement, and implementation processes and the lessons learned from a large and comprehensive MES project in Kenya. The MES process is intricate and time-consuming, requiring a team of skilled professionals. Prior to beginning the MES design, a well-planned hospital assessment can alleviate potential obstacles. Despite financial limitations, MES arrangement has the potential to enhance significantly healthcare services, particularly in low- and middle-income nations.